A new strategy for the reinforcement of paraffin-based fuels based on cellular structures: The armored grain — Mechanical characterization. (November 2020) - Bisin, Riccardo; Paravan, Christian; Alberti, Sebastiano; Galfetti, Luciano
Abstract: Paraffin waxes have been identified as promising hybrid rocket fuels. Though attractive from the ballistic point of view, these materials feature poor mechanical properties and, in particular, a brittle behavior making them unsuitable for application in operating systems. This study introduces a new strategy to enhance the mechanical properties of paraffin-based fuel grains manufactured at lab-scale. The implemented technique is based on the use of a 3D printed reinforcing structure embedded in the paraffin wax matrix and providing mechanical properties to the grain. This is named armored grain . The gyroid, a triply periodic cellular structure, is selected as a suitable reinforcing structure and its mechanical behavior is assessed by experimental and numerical investigations. Different 3D printable materials are considered, focusing the analysis on the differences due to their structural properties, compatibility and wettability with the paraffin fuel. In this paper, the mechanical properties of the gyroid-reinforced grains are evaluated by compression tests. The armored grains performance is compared to the mechanical behavior of fuel formulations in which reinforcement is pursued by blending the paraffin with thermoplastic polymers. The strength of the paraffin wax can be slightly enhanced by the addition of thermoplastic polymers. Under the investigated conditions (polymer mass fraction ≤ 10 % ), this reinforcing strategy yields blends with brittle behavior, while the armored grain provides a ductile behavior. The structural response of the armored grain can be tuned by exploiting different 3D printer polymers and relative densities (7%, 10%, 15%) for the gyroid reinforcement. Under the investigated conditions, the higher the relative density the stronger the mechanical properties. Albeit all the investigated polymers for gyroid reinforcement enhance the structural behavior of the paraffin wax, the nylon-based armored grain seems the most promising solution, featuring a 35% yield stress and a 296% yield strain increase over the paraffin baseline. Highlights: 3D printed gyroid as embedded reinforcing structure for paraffin-based fuels. Grain mechanical behavior influenced by infill and material of the reinforcement. Scaling laws to capture the mechanical behavior of gyroids. FEA for prediction of mechanical properties and print quality of gyroids. Grain mechanical behavior: from fragile to ductile thanks to the reinforcement.